Letting Beings Be: Review of What We Owe to Nonhuman Animals by Gary Steiner (2024) - Pepper, Angie (Humanimalia, 2024)
Review of: Gary Steiner, What We Owe to Nonhuman Animals: The Historical Pretensions of Reason and The Ideal of Felt Kinship. Routledge Human–Animal Studies Series. London: Routledge, 2024. x + 269 pp. £36.99 (pb), £135.00 (hb).